Exploring citizenship through the lens of suburban middle school students and civic images - Wessel, Kelly C. (Kansas State University, 2015)
This qualitative study explored middle school students’ conceptions of citizenship through the use of civic images. Citizenship education as the primary purpose for social studies education is firmly established; however, citizenship is an abstract concept. The definition and characteristics of citizenship, as well as research concerning the decline or evolution of civic behaviors, is inconclusive and oscillating. Recently adopted national and state social studies standards focus on inquiry and literacy skills, emphasizing the use of primary sources; namely historical documents. These texts are often insufficient curriculum drivers and generate a need to find alternative primary sources that scaffold and support students’ understanding. Images speak a familiar language and have been found to support student learning of history. This study fills a gap in the research regarding the use of images to teach citizenship, the purpose of social studies. Using a case study approach to research, multiple methods of data converged to address the research question, how do suburban middle school students understand citizenship through civic images? Twenty-seven eighth-graders enrolled in two Guided Study courses served as the research participants. The researcher spent two weeks at the start of the study, observing the students in their educational environment. Following the observations, for approximately eight weeks, students viewed a civic image and responded to a series of questions adapted from the Stanford History Education Group’s Historical Thinking Skills Chart (2006). At the conclusion of the eight weeks, the researcher conducted focus group interviews with each class and individual interviews with eight randomly selected students and the participating teacher. The results of this study support the use of images as instructional resources to teach abstract concepts, particularly citizenship, as well as support the use of images as primary sources to teach inquiry and literacy skills. The civic images deepened student understanding of civic and historical concepts and, more importantly, they informed students’ definitions of citizenship. Equality and community were revealed by the data as defining characteristics of citizenship for the students involved in this study, supporting previous research that members of younger generations are redefining what it means to be a good citizen.
Keywords: Citizenship education; Civic images; Social studies; Adolescent development; Visual literacy; Middle school students; Social Sciences Education (0534)